Creation of Learning Motivation in the Process of Cognitive Learning in Teaching Music to 12-13 Years Old Pupils - Kepule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Creation of learning motivation is one of the main problems of the school. Motivation is the basis for self-improvement; its fulfillment facilitates development of the personality and encourages a pupil to study better in order to reach the set goal. If the teacher knows the reasons for the learning motivation of the pupils, he or she can select the methods and techniques, which could stimulate the inquiry process, and in addition to development of various skills and abilities would increase also the pupils’ learning motivation. The purpose of the article - to identify the factors for creation of learning motivation for 12-13 years old pupils, based on studying and interpretation of scientific literature and teaching experience. Methods – analysis of scientific literature, questionnaires and data processing using SPSS software. The study actualizes relation of the pupils’ learning motivation with their learning activities in the cognitive learning process during the music lesson. The results obtained as the result of the study provide for an opportunity to have discussions regarding the understanding of pupils regarding the need to study.